Cuento Animado 3d sobre la Importancia de la práctica de Deportes en los niños pequeños - De la Cruz Figueroa, Candice Estefanía (2015)
This is a 3D animation short film that seeks to connect children with sports instead of Video Games, demonstrating that fun can be even greater if they play and learn in real life. The length of this short film is approximately one minute.